Membentuk Calon Guru Adaptif Abad 21: Pelatihan Perencanaan Pembelajaran Inovatif Kurikulum Merdeka bagi Mahasiswa Pendidikan Biologi - Ariyati, Eka; Marlina, Reni; Yokhebed, Yokhebed; Salim, Salim; Vidiarto, Rizki Agung; Ervina, Tri; Nadia, Zahra (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Creativity is one of the important points in the world of education, one of which is creativity in designing creative and innovative learning activities to anticipate or answer educational challenges in the 21st century. This service activity aims to find out the ability of biology education students in preparing innovative learning plans based on the independent curriculum. The method in this service is observation and analysis of problems and needs, determination of activity schedules, core activities/training with interactive lectures, workshops, presentation discussions, and reflections. The results of the service hone students' creativity in designing learning plans, where the resulting learning planning (100%) shows conformity with the principles of the Independent Curriculum, and 85% of them show strong innovation elements. Through practice-based training, workshops, and reflective discussions, students gain concrete experience in developing teaching modules that are contextual, differentiated, and oriented towards learning outcomes and authentic assessments. This activity also has strategic implications for the development of study programs and LPTK in preparing prospective teachers who are professional, adaptive, and responsive to the dynamics of the Independent Curriculum.